Answer:
(b) 32x²∛(2x) -8x³
Explanation:
You want to simplify the radical expression ...
4x∛(4x²)(2∛(32x²) -x∛(2x))
Radical rules
The relevant rules of radicals are ...
∛(a³b) = a∛b
(∛a)(∛b) = ∛(ab)
Simplify
We can eliminate the parentheses using the distributive property.
![4x\sqrt[3]{4x^2}\left(2\sqrt[3]{32x^2}-x\sqrt[3]{2x}\right)=4x\sqrt[3]{4x^2}\cdot2\sqrt[3]{32x^2}-4x\sqrt[3]{4x^2}\cdot x\sqrt[3]{2x}\\\\=8x\sqrt[3]{128x^4}-4x^2\sqrt[3]{8x^3}=8x\sqrt[3]{(4x)^3\cdot2x}-4x^2\sqrt[3]{(2x)^3}\\\\=(8x)(4x)\sqrt[3]{2x}-(4x^2)(2x)=\boxed{32x^2\sqrt[3]{2x}-8x^3}\qquad\text{choice B}](https://img.qammunity.org/2023/formulas/mathematics/college/f3wbbzyrkunl5sb3sk8vyahhwjoi2vni9y.png)
<95141404393>